Asperger syndrome and legal issues - Woodbury-Smith, Marc (Henry Stewart Talks, 2010)
Risk of law breaking behaviour in Asperger Syndrome, Factors associated with problematic and law breaking behaviours, Prevalence of law breaking behaviour, Asperger Syndrome and the criminal justice system